2014
DOI: 10.1007/s00705-014-2011-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of differential gene expression in kidney tissues of moribund and surviving crucian carp (Carassius auratus gibelio) in response to cyprinid herpesvirus 2 infection

Abstract: Cyprinid herpesvirus 2 (CyHV-2) has recently been associated with high mortality of cultured crucian carp (Carassius auratus gibelio) in eastern China. In this study, we established a real-time PCR method to confirm viral infection of crucian carp and to quantify CyHV-2 particles obtained by sucrose gradient centrifugation from diseased fish. Virus-free crucian carp were artificially infected with CyHV-2 using an injection method, which resulted in a dose-dependent death rate. In situ hybridization analysis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 21 publications
3
83
0
Order By: Relevance
“…Owing to the highly intensifying and seriously crowding of monoculture, gibel carp has been suffered by a series of pathogens [73]. Since 2009, an epizootic with acute gill hemorrhages and high mortality has outbroken in cultured gibel carp [74]. The complete genome sequencing of the virus isolated from the tissues of diseased gibel carp showed the Ca HV was most closely related to CyHV-2 [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Owing to the highly intensifying and seriously crowding of monoculture, gibel carp has been suffered by a series of pathogens [73]. Since 2009, an epizootic with acute gill hemorrhages and high mortality has outbroken in cultured gibel carp [74]. The complete genome sequencing of the virus isolated from the tissues of diseased gibel carp showed the Ca HV was most closely related to CyHV-2 [15].…”
Section: Discussionmentioning
confidence: 99%
“…By using PCR assay, CyHV-2 was first detected in gibel carp in Hungary [81]. Recently, it has been detected in many main culture regions of gibel carp [74] and caused huge economic loss. The experimental infection of indigenous Cyprininae species in Japan, such as ginbuna C. auratus langsdorfii , nagabuna C. auratus buergeri , nigorobuna C. auratus grandoculis and common carp, suggested that Japanese Carassius fish species possess different ability to depress the replication of CyHV-2 [82].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, after cyprinid herpesvirus disease became widely reported in the world, (especially in China) [145][146][147], numerous studies on cyprinid herpesviruses and identification of immune-related genes have been conducted [148][149][150]. It is envisaged, therefore, that new insight and better understanding of these cyprinid herpesviruses will emerge and lead to efficient antiviral approaches being developed in the near future.…”
Section: Herpesvirus Genomesmentioning
confidence: 99%